GenoType MTBDRplus assay for screening and characterization of isoniazid and rifampicin resistance‐associated mutations in multidrug‐resistant Mycobacterium tuberculosis from India. (1st November 2017) - Sethi, S.; Yadav, R.; Singh, S.; Khaneja, R.; Aggarwal, A.; Agarwal, P.; Behera, D.
Abstract: Multidrug resistant tuberculosis (MDR‐TB) is rising and the World Health Organization has recommended the line probe assay (LPA) for screening. In this study we assess LPA at a tertiary care centre from North India in 1758 samples from suspected MDR‐TB cases. All smear‐positive and/or Mycobacterium tuberculosis culture confirmed cases ( n = 1170) were subjected to the GenoType‐MTBDR assay. Amongst these the majority were retreatment cases, smear‐positive at diagnosis ( n = 637). An MDR prevalence of 7·8% was observed with the highest cases reported amongst MDR contacts (33·3%). The most common rifampicin resistance encoding mutation seen overall and in individual patient groups was H531L (53·3%). A higher prevalence of H526D mutation was observed in retreatment cases, smear‐positive at 4 months of anti‐tubercular therapy vs other patient groups ( P = 0·052). The most common mutation encoding isoniazid resistance was S315T1 in the kat G (79·9%) and C‐15T in the inh A gene (91·1%). Thirty rifampicin and nine isoniazid resistant isolates had wild type gene deletion but no detectable mutation by LPA. Although LPA is a practical and rapid screening method for most mutations expected to result in MDR‐TB, we observed that it only detects the known major mutations in specific genes. Such studies can provide the knowledge required to formulate customized strips based on prevalent mutations in our region and in specific patient groups. Significance and Impact of the Study: To the best of our knowledge this is the largest study evaluating the GenoType‐MTBDR line probe assay from India. We have studied the prevalence of mutations encoding rifampicin and isoniazid resistance in different patient groups based on criteria for multidrug resistance (MDR) suspicion. The translational impact of this study is in the design of customized country‐ or region‐wise line probe assay strips. The identification of a few mutations in particular patient groups and the detection of wild type deletion mutants with no observable mutations both point toward the need for such customization enabling us to combat the rising trend of MDR tuberculosis.